The Effect of E-Service Quality, E-Trust, and E-Customer Satisfaction on E-Customer Loyalty on the Use of the Halodoc Application (Study: Users of the Halodoc Application in Surabaya City) - Sri Linda Handayani; Budi Prabowo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
The competition in the digital health industry to maintain and establish long-term relationships with customers, especially the Halodoc application, is the reason for this study. The purpose of this study is to analyze the effect of e-service quality, e-trust, and e-customer satisfaction on e-customer loyalty in Halodoc application users. The research method used is a quantitative approach with an associative research type. Data was collected through a questionnaire distributed to 100 respondents who were Halodoc application users. The data analysis technique used was multiple linear regression with the help of the SPSS program. The results of the analysis showed that simultaneously and partially, the three independent variables, namely e-service quality, e-trust, and e-customer satisfaction, had a positive and significant effect on e-customer loyalty. This study concludes that in order to maintain and encourage customer loyalty, companies need to focus on optimizing service quality, maintaining trust consistently, and increasing high customer satisfaction in order to maintain customer loyalty.